Emergence and Early Development of Dietitian as an occupation in Argentina - José Buschini (Avances del Cesor, 2016)
This paper analyses the emergence and early development of the dietitian profession -currently known as nutritionist- in Argentina. It focuses on the projects by which this occupation was created -considering the way in which formative requisites and incumbencies were conceived-, the realization of those projects and the access to labor market by the first graduated dietitians. Furthermore, aided by the sociology of professions, this paper aims to understand some peculiarities linked to the creation and early development of this occupation: on the one hand, some aspects of its activities were subordinated to medicine and on the other, its access was restricted to women. In relation to those two characteristics, that the occupation of dietitian was the result of a physician’s project, while medicine was mainly a male occupation.